Screening of media composition for bioprotein production using coconut dregs as a new potential substrate - Nor Hidayah Bohari (School of Bioprocess Engineering, University Malaysia Perlis, 2011)
The world s population are increased and the demands for natural resource of food especially protein source are limited. Only a rational and sustainable exploitation will continue to produce enough and nutritive food, to satisfy the future needs of humankind. Bioprotein production is one of the most promising breakthroughs of biotechnological innovations in animal feed industry. Due to its increasing demand, the utilization of coconut dregs as a novel substrate and cheaper carbon source for production of bioprotein is found necessary for the fulfilling animal feed industrys demand. In this present study, screening of three different strains Aspergillus niger (ATCC 16404), Saccharomyces cerevisiae (ATCC 9080) and Phanerochaete chrysosporium (ATCC 24725), was done for bioprotein production by solid state fermentation process. Aspergillus niger produced the highest amount of protein on the sixth day, with the amount of 427 mg/L. The performance of the selected strains, Aspergillus niger was enhanced by identification of the most significant media composition with different percentage value according to the Plackett-Burman Design. Among the seven parameters of media compositions, NH4NO3, MgSO4.7H2O and CuSO4.5H2O were found to have the confidence level above 95 percent and considered to affect bioprotein production. This study would provide a better alternative in agricultural products by converting agriculture waste to valuable and quality product bioprotein, which can be used as supplement and additive in the animal feed and food as well as in chemical and pharmaceutical industries.